Teaching Process Skills to Pre-Engineers using Situated Learning – A Case Study - Maher, Pamela A.; Bailey, Janelle M.; Tucka, Allan M. (International Journal of Engineering Pedagogy (iJEP), 2018)
In this case study, undergraduate students presented physics concepts to patrons at a planetarium. This created an early opportunity for these pre-professionals to practice the process skill of oral communication to a lay audience. The case study resulted from working with students participating in a grant called the da Vinci project. It reports on a situated experience pre-engineering and calculus-based physics students had working with their professor to create a brochure and present a physics concept to patrons visiting a public planetarium. Working closely with their professor, students were able to use this required professional skill in a real world (situated) context. This opportunity helped bridge the gap between these pre-professionals’ experiences in training and in their careers in STEM fields. Thirty students attending a two-year college in the Southwestern US self-selected to participate in the project. Each student participant built a kit-based model of a machine, designed an informational flyer aligned to state K-12 physical science standards, and presented informally to the public visiting a planetarium. Data were collected from the students via written reflections before and after the presentation and from email correspondence with their professor. Qualitative analyses of these reflections assessed the students’ progress toward a finished presentation. Results suggest that obstacles to public speaking fluency come from the fear of making mistakes or giving out misinformation. Opportunities to engage in informal public speaking helped overcome these obstacles. Students demonstrated increased confidence in their ability to share their knowledge with the public after undergoing guided informal speaking practice. The opportunity for students to practice public speaking during their undergraduate training can increase confidence and better prepare them for a career.